Dynamics of The U.S.-China Relationship Post-Firewall Malware Attack - Boer, Dara Cantika Putriadin; Wardhana, Fahriy Aulia; Arifin, Muhammad; Zahra, Nadhira Fitria; Triwahyuni, Dewi (International Journal of Research and Applied Technology (INJURATECH), 2025)
This study analyzes the impact of the Firewall Malware attack on US-China bilateral relations and its implications for global cybersecurity policy. The attack, detected in late 2024, exploited firewall vulnerabilities in US government and private sector systems, leading to significant data breaches. The US attributed the attack to a hacker group allegedly affiliated with the Chinese government, while China denied the allegations, escalating geopolitical tensions and undermining the 2015 US-China Cyber Agreement. Using a qualitative research methodology with a case study approach, this study examines government reports, cybersecurity analyses, policy statements, and media coverage, applying content analysis to assess geopolitical consequences and the effectiveness of international cybersecurity agreements. The findings reveal that the attack intensified US-China tensions, prompting sanctions, policy shifts, and heightened cybersecurity measures. The US reinforced its cyber defence strategies and imposed economic restrictions, while China sought to build alliances to counter the accusations. The study highlights the failure of existing international cybersecurity agreements in preventing state-sponsored cyber threats, emphasizing the urgent need for stronger global cooperation and regulatory frameworks to mitigate cyber conflicts and enhance cybersecurity resilience.